The Influence of Leadership, Discipline, and Compensation on the Performance of Police Officers with Motivation as an Intervening Variable at the Banyuwangi Police Resort - Vivien Helfaria Analiz; Hadi Prayitno; Yuslinda Dwi Handin (POLITICO, 2026)
This study examines the effects of leadership, discipline, and compensation on the performance of police officers, with work motivation as an intervening variable, at Polresta Banyuwangi. The study is grounded in differences between empirical findings and theoretical perspectives regarding the roles of leadership, discipline, and compensation in improving employee performance, as well as inconsistencies in previous research concerning the mediating function of work motivation. Using an explanatory research design and a quantitative approach, a sample of 219 respondents was selected from a population of 484 officers using Slovin’s formula and proportional random sampling. Data were collected through observation and Likert-scale questionnaires and analyzed using Partial Least Squares (WarpPLS 8.0). The results indicate that leadership has a positive and significant effect on both work motivation and performance. Discipline has a negative and significant effect on work motivation but a positive effect on performance. Compensation has a positive and significant effect on both work motivation and performance. Work motivation has a negative and significant effect on performance, indicating a tendency toward extrinsic motivation orientation. Model testing was conducted through partial and simultaneous relationship analyses using the coefficient of determination (R²). The results show that leadership, discipline, and compensation jointly affect work motivation, while leadership, discipline, compensation, and work motivation simultaneously influence the performance of police officers. These findings recommend strengthening transformational leadership, balancing disciplinary enforcement with a humanistic coaching approach, and improving the compensation system to foster intrinsic motivation and enhance public service performance at Polresta Banyuwangi.